Perspective chapter: early management of dental trauma in the era of COVID-19 - Chi Adam, Khairul Bariah; Hassan, Haszelini; Subramaniam, Pram Kumar; Ismail, Izzati Nabilah; Harun, Nor Adilah; Mustafa, Nazih Shaban (IntechOpen, 2023)
Traumatic dental injuries are emergencies that must be treated promptly and properly to reduce the suffering, costs, and time for patients and parents. However, since the coronavirus disease 2019 (COVID-19) outbreak was declared a pandemic on March 11, 2020, most dental care facilities in the affected countries have been completely closed or have been only providing emergency treatment. This can partly be a result of the lack of universal protocol or guidelines regulating the dental care provision during such a pandemic, especially in the management of dental trauma. This lack of guidelines has the potential to both promote the spread of nosocomial COVID-19 through oral health care facilities and deny people in need of immediate treatment. Moreover, ceasing dental care provision during such a period will incense the burden on hospitals’ emergency departments that are already struggling with the pandemic. Therefore, this chapter elaborates on the importance of early management of dental trauma by sharing local guidelines and experience with a proposed algorithm for the early management of dental trauma during the emergence of COVID-19.